Economic Analysis of the Impact of Applying the Marketing Information System on the Competitive Advantage in Food Industries Companies in Iraq - Al-Thamir, Samira Nema Kamil (Advances in Social Sciences Research Journal, 2025)
The contemporary rapid development in marketing information systems has contributed to the process of gaining a competitive advantage for most companies of all kinds in the world, as the process of gaining a competitive advantage is based mainly on the quality of information available and to use in facing problems. The issue of competitive advantage has become one of the topics that companies care about a lot. In light of competition and the speed of change in the desires and needs of customers, companies seek continuous development to achieve excellence, stay in the markets, and gain strong competitive advantages to face the intensity of competition. In this research, the marketing information system (databases, marketing research, marketing intelligence, decision making assistance system) was identified on the competitive advantage of food industry companies in Iraq, where a special questionnaire was distributed to corporate officials and marketing managers in (35) companies from Food industry companies, The analysis was done using regression analysis. The research concluded that there is a positive effect of the components of the marketing information system on the indicators of competitive advantage, namely: market share, business reputation, and customer satisfaction, while it was found that achieving excellence and employing technology does not have a positive effect by the components of the marketing information system in the companies under study. Based on the results of the research, a set of recommendations aimed at enhancing the role of the marketing information system in achieving the competitive advantage of the food industries companies in Iraq was put forward.